2010
DOI: 10.1136/ard.2008.099945
|View full text |Cite
|
Sign up to set email alerts
|

National cohort study of reproductive risk factors for rheumatoid arthritis in Denmark: a role for hyperemesis, gestational hypertension and pre-eclampsia?

Abstract: One-child mothers and young parents are at increased risk of RA later in life, possibly due to socioeconomic factors. The novel finding of a significantly increased risk of RA in women whose pregnancies were complicated by hyperemesis, gestational hypertension or pre-eclampsia might reflect reduced immune adaptability to pregnancy in women disposed to RA or a role of fetal microchimerism in the aetiology of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 44 publications
3
50
1
1
Order By: Relevance
“…Hormonal and immunological imbalances have been suggested to be involved in all these different abnormal pregnancy outcomes [16e20]; conditions that might also contribute to the development of ADs. We have previously shown that spontaneous abortions, missed abortions and stillbirths are associated with increased risk of SLE and that hyperemesis, gestational hypertension and preeclampsia are associated with increased risk of rheumatoid arthritis [21,22]. In contrast, we observed no association between pregnancy complications or losses and subsequent risk of multiple sclerosis [23].…”
Section: Introductioncontrasting
confidence: 78%
“…Hormonal and immunological imbalances have been suggested to be involved in all these different abnormal pregnancy outcomes [16e20]; conditions that might also contribute to the development of ADs. We have previously shown that spontaneous abortions, missed abortions and stillbirths are associated with increased risk of SLE and that hyperemesis, gestational hypertension and preeclampsia are associated with increased risk of rheumatoid arthritis [21,22]. In contrast, we observed no association between pregnancy complications or losses and subsequent risk of multiple sclerosis [23].…”
Section: Introductioncontrasting
confidence: 78%
“…A recent publication showed a skewed placental weight‐to‐birth weight ratio, possibly reflecting suboptimal placentation, but this was found only in women with HG who were carrying female fetuses 35. Moreover, HG is reported to be associated with subsequent increased risk of autoimmune diseases 23, 24. A Danish study found a statistically significant association between HG and autoimmune diseases in general and in particular between HG and Sjögren's syndrome, Graves’ disease, rheumatoid arthritis, pernicious anaemia, coeliac disease, Crohn's disease, ulcerative colitis and psoriasis 23.…”
Section: Discussionmentioning
confidence: 99%
“…Although HG is the most common reason for hospitalisation during the first trimester,22 little is known about the long‐term consequences of HG exposure. Some studies have reported an association between HG and risk of autoimmune disease later in life 23, 24. A recent study investigating cancer risk after HG exposure reported an inverse association between HG and overall cancer risk 25.…”
Section: Introductionmentioning
confidence: 99%
“…While results of published studies on the association between pregnancy and SLE are contradictory [5,6], evidence suggests that the risk of multiple sclerosis onset is reduced during gestation and increased in the first 6 months after pregnancy [7,8]. It is unclear, despite much investigation, whether there is an association between parity and the risk of rheumatoid arthritis [9][10][11]. The currently available data do not provide convincing evidence that parity provides an explanation for the female predominance in the majority of autoimmune conditions.…”
Section: Introductionmentioning
confidence: 99%